Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Perdana, Aryudi Indra; Sutiarso, Sugeng; Triana, Mella (FKIP Universitas Mataram, 2025)
This study aims to determine the effect of problem-based learning model on students' mathematical critical thinking skills. The population of this study is all seventh grade students of SMP Negeri 1 Natar even semester of the 2023/2024 academic year as many as 371 students distributed into eleven classes, namely VII A to VII K. Sampling was carried out using purposive sampling technique, so that VII A class of 34 students was selected as the experimental class and VII D of 33 students as the control class. The design used was pretest-posttest control group design. The data in this study are quantitative data obtained through the mathematical critical thinking ability test. Based on the Mann-Whitney U test results, it was found that the improvement in mathematical critical thinking skills of students who participated in learning with problem-based learning was higher than the improvement in mathematical critical thinking skills of students who participated in conventional learning. In addition, based on the results of the proportion test, it was found that more than 60% of students who participated in problem-based learning were categorized as good. So it can be concluded that the problem-based learning model has an effect on students' mathematical critical thinking skills.